Interactive Video Simulation for Remote Healthcare Learning - Musa, Dahlia; Gonzalez, Laura; Penney, Heidi; Daher, Salam (Frontiers in Surgery, 2021)
Simulation is an essential component of healthcare education as it enables educators to replicate clinical scenarios in a controlled learning environment. Simulation has traditionally been conducted in-person through the use of manikins, however, the COVID-19 pandemic has challenged the practice of manikin simulation. Social distance constraints were enforced during the pandemic to reduce the potential spread of the virus and as a result, many educators and students were denied physical access to their universities’ simulation facilities. Healthcare educators sought remote alternatives to manikin simulation and many resorted to instructional videos to educate their learners. While the use of videos increases safety, passively watching videos lacks interactivity which is an important component of simulation learning. In response to these challenges, we developed an interactive video simulation software that uses educators’ existing video content to conduct a simulation remotely, thereby promoting safety during the pandemic while also meeting the interactivity standards of best practice for healthcare simulation. In this paper, we compare the interactive video simulation to the current practice of watching non-interactive video of a simulation using the same content. We found that interactivity promotes higher order learning, increases teamwork and enhances the perception of authenticity. Additionally, the majority of participants demonstrated positive reception of the interactive simulation. The simulation software provides the safety desired of a remote simulation during the pandemic while also engaging students in interactive learning experiences.